2018
DOI: 10.1186/s12970-018-0214-2
|View full text |Cite
|
Sign up to set email alerts
|

Calorie restriction regime enhances physical performance of trained athletes

Abstract: BackgroundCaloric restriction induces mitochondrial biogenesis and improves physical fitness in rodents. We aimed to provide evidence of how caloric restriction affects the body composition and physical performance of trained athletes and to evaluate the possible impact of an every-other-day feeding diet on nutritional deficiencies of micronutrients and essential fatty acids.MethodsThe study was performed with 12 healthy male athletes by carrying out a 33% caloric restriction with respect to their usual diet. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…BMI may have a positive impact on short-term goals and reducing weight prior to a competition or a climbing trip may give short-term benefits 15–17. This effect may however be undermined by fatigue or injuries due to malnutrition as keeping a low BMI over time impacts general overall health and increases risk of overuse injuries 9 18.…”
Section: Discussionmentioning
confidence: 99%
“…BMI may have a positive impact on short-term goals and reducing weight prior to a competition or a climbing trip may give short-term benefits 15–17. This effect may however be undermined by fatigue or injuries due to malnutrition as keeping a low BMI over time impacts general overall health and increases risk of overuse injuries 9 18.…”
Section: Discussionmentioning
confidence: 99%
“…The available evidence is insufficient to determine whether total energy intake per day or macronutrient and micronutrient proportions in the diet are associated with the prevalence of injury in endurance runners [170]. Further investigations are needed to determine whether caloric restriction is related to a higher incidence of injury, as diets with reduced calorie intake are gaining popularity [171] and no evidence exists on this topic. Finally, several dietary supplements are consumed by athletes to alleviate pain and to reduce the risk of injury based on the claims of supplement manufacturers.…”
Section: Factors Associated With Running-related Injuriesmentioning
confidence: 99%
“…Together, these data indicate that weight loss was primarily achieved via energy restriction. (Finaud et al, 2006;Merrells et al, 2008;Reljic et al, 2015) or a reduction (Pons et al, 2018), whereas others reported an increase (Rankin et al, 2006;Yanagawa et al, 2015). This discrepancy may be related to factors such as the duration of the energy restriction, the biomarkers utilized for the measure of oxidative stress, and the training load employed during the energy restriction.…”
Section: Discussionmentioning
confidence: 95%